P6. Digital breast tomosynthesis: Dose and image quality assessment. (December 2016) - Fezzani, K.L.; Sage, J.; Fitton, I.; Hadid, L.; Moussier, A.; Pierrat, N.; Martineau, A.; Etard, C.
Abstract : Introduction: Digital Breast Tomosynthesis (DBT) offers a gain in sensitivity and in specificity for the detection of breast cancers compared to 2D mammography, due to reduction of the tissues' overlapping. DBT is already used in many centers in France. The introduction of this technique within the French breast cancer screening program is being considered by the authorities for the coming years. As it has been done for 2D digital mammography, a protocol for quality control must be developed specifically for this technic. It is therefore necessary to increase our knowledge of tomosynthesis systems and of Image quality phantoms proposed by manufacturers. The aim of the study is to compare different DBT systems in term of dose and image quality. The evaluation of different image quality phantoms could lead to recommendations for internal quality control (regulatory or not). Methods: Five French hospitals with three different tomosynthesis systems and seven specific phantoms have been included in the study. Average Glandular Dose and Signal Difference to Noise Ratio are assessed for different thicknesses of PMMA. Regarding image quality, reconstructed images are analyzed on global score, spatial resolution, geometrical distortion and homogeneity aspects. Results: Preliminary results on dose and image quality for different models and different acquisition modes will be presented. Phantoms' sensitivity at different dose levels will be discussed as well. Conclusions: The variety of DBT systems design leads to an expected variability in terms of image quality and dose with breast thickness. Particular attention should be paid to the increased dose in comparison with 2D digital mammography. Works at a national level on the regulatory quality control of tomosynthesis systems should be initiated as soon as possible. The results of this study are expected to contribute to the national discussion on this topic.